The relationship between atrial fibrillation and frailty in community-dwelling older adults. (September 2020) - Yang, Ming-Ting; Wu, Yen-Wen; Chan, Ding-Cheng; Chien, Meng-Yueh
Highlights: Atrial fibrillation was associated with frailty status in the present study. Participants with atrial fibrillation were observed with poorer physical function. Frailty screening in older adults with atrial fibrillation is suggested. The frailty phenotype might be applicable for the earlier frailty screening. Abstract: Objectives: (1) To compare the frailty status between community-dwelling older adults with and without atrial fibrillation (AF) in Taiwan and (2) to test the hypothesis that AF is associated with frailty in community-dwelling older adults. Methods: We conducted a cross-sectional study in several communities in Taipei. AF was confirmed by electrocardiogram recordings or medical diagnosis. Frailty status was assessed using both the Cardiovascular Health Study (CHS) frailty phenotype and Edmonton Frail Scale (EFS). Results: A total of 207 community-dwelling older adults voluntarily participated in this study, and 38 had AF. There was a significantly higher percentage of frailer (prefrail and frailty) older adults in the AF group (69 % vs. 36 %, p < 0.001) according to CHS phenotype, but no significant difference was detected by EFS criteria (92 % vs. 92 %, p = 0.966). The AF group showed significantly lower grip strength in men (26.8 ± 8.3 vs. 33.0 ± 6.9 kg, p = 0.006), walking speed (1.1 ± 0.3 vs. 1.2 ± 0.3 m/s, p = 0.003), and Timed Up and Go performance (8.8 ± 2.4 vs. 7.0 ± 1.9 s, p < 0.001) than the control group. The multiple logistic regression model showed that AF was an independent factor associated with frailer community-dwelling older adults after adjusted for covariates (odds ratio, 3.02; 95 % confidence interval, 1.32–6.89, p = 0.009). Conclusion: Community-dwelling older adults with AF showed a significantly higher percentage of frailer individuals and lower physical function than those without AF. Furthermore, AF was an independent predictor of frailer community-dwelling older adults.